Correlation of omega-3 levels in serum phospholipid from 2053 human blood samples with key fatty acid ratios - Holub, Bruce J (BioMed Central, 2009)
BACKGROUND: This research was conducted to explore the relationships between the levels of omega-3 fatty acids in serum phospholipid and key fatty acid ratios including potential cut-offs for risk factor assessment with respect to coronary heart disease and fatal ischemic heart disease. METHODS: Blood samples (n = 2053) were obtained from free-living subjects in North America and processed for determining the levels of total fatty acids in serum phospholipid as omega-3 fatty acids including EPA (eicosapentaenoic acid, 20:5 n-3) and DHA (docosahexaenoic acid, 22:6 n-3) by combined thin-layer and gas-liquid chromatographic analyses. The omega-3 levels were correlated with selected omega-6: omega-3 ratios including AA (arachidonic acid, 20:4n-6): EPA and AA:(EPA+DHA). Based on previously-published levels of omega-3 fatty acids considered to be in a 'lower risk' category for heart disease and related fatality, 'lower risk' categories for selected fatty acid ratios were estimated. RESULTS: Strong inverse correlations between the summed total of omega-3 fatty acids in serum phospholipid and all four ratios (omega-6:omega-3 (n-6:n-3), AA:EPA, AA:DHA, and AA:(EPA+DHA)) were found with the most potent correlation being with the omega-6:omega-3 ratio (R(2 )= 0.96). The strongest inverse relation for the EPA+DHA levels in serum phospholipid was found with the omega-6: omega-3 ratio (R(2 )= 0.94) followed closely by the AA:(EPA+DHA) ratio at R(2 )= 0.88. It was estimated that 95% of the subjects would be in the 'lower risk' category for coronary heart disease (based on total omega-3 ≥ 7.2%) with omega-6:omega-3 ratios <4.5 and AA:(EPA+DHA) ratios <1.4. The corresponding ratio cut-offs for a 'lower risk' category for fatal ischemic heart disease (EPA+DHA ≥ 4.6%) were estimated at < 5.8 and < 2.1, respectively. CONCLUSIONS: Strong inverse correlations between the levels of omega-3 fatty acids in serum (or plasma) phospholipid and omega-6: omega-3 ratios are apparent based on this large database of 2053 samples. Certain fatty acid ratios may aid in cardiovascular disease-related risk assessment if/when complete profiles are not available.